Chemical and nutritional characterization of loengo (Anisophyllea boehmii) fruits as a source of important bioactive with impact on health - Lofa, Alcides Morais; Mourato, Miguel Pedro; Prista, Catarina; Sousa, Isabel; Ferreira, Ricardo Boavida (Frontiers in Food Science and Technology, 2024)
IntroductionFruits are vital for human health, providing nutrients and other compounds linked to protection against different diseases. Loengo (Anisophyllea boehmii Engl.) produces an edible stone fruit, plum-shaped (drupe), dark blue and maroon or carmine in the ripening stage, which is generally, consumed fresh in the production areas. Characterization of this fruit will contribute to estimate its nutritional and pharmaceutical potential impact. The present work aimed at the physic-chemical, nutritional and antioxidant activity characterization of loengo fruit.MethodsSoluble solid contents (SSC) in the pulp were assessed in juice, at room temperature. Total protein was determined using the Dumas method. In what concerns the mineral composition were determined by ICP-OES. Organic acids identification and quantification was accomplished using a high-performance liquid chromatography (HPLC) system. The total polyphenol contents (TPC) were determined in 96-well microplate assays. Antioxidant activity were determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and the ferric reducing antioxidant power (FRAP) assay.Results and discussionComposition, in terms of fresh matter is as follows: pulp soluble sugar content (refractometer) is 19.5% ± 0.02%, and pulp titratable acidity 1.2% ± 0.1% expressed in citric acid; total protein content is 7.4% ± 0.02%, 8.0% ± 0.1%, 16.9% ± 0.2%, for the peel, pulp and seed, respectively. In what concerns the mineral composition, the results obtained show that it is a good source of minerals, mainly potassium and phosphorus, but also calcium, sulfur, and magnesium, with the pulp richer in potassium, the seed in phosphorus, and the peel in calcium. As expected, the pulp showed the highest total soluble sugar content, whereas the seed had the lowest. The main sugars found in the pulp were glucose and fructose. In the peel citric acid was the main organic acid found, together with malic, oxalic, and ascorbic acids. Most antioxidant activity was found in the seed. The results of this work provide important information to recommend the consumption of this fruit for its sweet taste, chemical and nutritional composition, and, most of all, for its richness in total phenolic compounds for it potential to formulate nutraceutical foods.